Comparing cyberbullying perpetration on social media between primary and secondary school students. (June 2017) - Ho, Shirley S.; Chen, Liang; Ng, Angelica P.Y.
Abstract: This study aims to explore factors associated with cyberbullying perpetration on social media among children and adolescents in Singapore, based on the theory of reasoned action and the parental mediation theory. More specifically, the relationships between attitude, subjective norms, descriptive norms, injunctive norms, and active and restrictive parental mediation with cyberbullying perpetration on social media were investigated. Moreover, we examined the moderating effect of age on the relationship between parental mediation and cyberbullying perpetration. Multi-stage cluster sampling was used, in which 635 upper primary school children (i.e., Primary 4 to 6 students) and 789 secondary school adolescents participated in our survey. The results revealed that attitude, subjective norms, and the two parental mediations – active and restrictive mediation – were negatively associated with cyberbullying perpetration on social media. Age was a significant moderator of both parental mediation strategies and cyberbullying perpetration. Implications and limitations of this study were discussed. Highlights: We examine cyberbullying perpetration on social media among children & adolescents. A large-scale nationally representative survey ( N = 1424) was conducted in Singapore. Attitude and subjective norms predicted cyberbullying perpetration on social media. Active and restrictive parental mediation predicted cyberbullying perpetration. Age moderated the effects of parental mediation on cyberbullying perpetration.